Astragalus wulingensis (Leguminosae), a new species from Hunan China - Li, Jiaxiang; Yu, Xunlin (Phytotaxa, 2014)
A new species of Astragalus Linn. (Leguminosae) from Wuling Mountain of Hunan province, China, Astragalus wulingensis Jia X. Li & X. L. Yu sp. nov. is described, illustrated, and compared with its close relatives. It belongs to section Lotidium Bunge, subgen. Astragalus Bunge. The new species is endemic to Wuling Mountain in NW Hunan Province and has limited populations and vulnerable habitat. Astragalus wulingensis is assessed as Critically Endangered (CR B2c) according to IUCN Red List criteria.